THE EFFECT OF TAKE AND GIVE STRATEGY ON STUDENTS TENSES MASTERY (A Study at The Tenth Grade Students of SMA Negeri 1 Angkola Barat 2017/2018 Academic Year) - Yessi Serviki Hutagalung (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of the research is to know the application of take and give strategy on students tenses mastery at the tenth grade of SMA Negeri 1 Angkola barat, to know before and after use take and give strategy at the tenth grade of SMA Negeri 1 Angkola Barat, and to know whether there is any significant effect of take and give strategy on students tenses mastery at the tenth grade of SMA Negeri 1 Angkola Barat 2017/2018 Academic Year. The population in this research is all of the tenth grade students are 198. The sample are 33 students which taken by systematic sampling. The research method is use by experimental method. Collecting the data by observation sheet and test as an instrument. The result mean score of the application take and give strategy is 3.7, based on the technique of analysis data the criterion of score take and give with categorized “Very Good”. To know the result of the data, the researcher analysis data by use the formula of ttest. The result of the data analysis show that of ttest = 9.82,meanwhile ttable 2.03. It means that ttest is higher than ttable. So, the hypothesis is accepted. It means that there is significant effect of take and give strategy on students tenses mastery at the tenth grade of SMA Negeri 1 Angkola Barat. Keywords: Take and Give Strategy, Tenses Mastery